2018
DOI: 10.2139/ssrn.3263375
|View full text |Cite
|
Sign up to set email alerts
|

Debt Holder Monitoring and Implicit Guarantees: Did the BRRD Improve Market Discipline?

Abstract: This paper argues that the introduction of the Banking Recovery and Resolution Directive (BRRD) improved market discipline in the European bank market for unsecured debt. The different impact of the BRRD on bank bonds provides a quasi-natural experiment that allows to study the effect of the BRRD within banks using a difference-indifference approach. Identification is based on the fact that (otherwise identical) bonds of a given bank maturing before 2016 are explicitly protected from BRRD bail-in. The empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This effect became significantly relevant after Italian authorities decided to resolve four small banks in November 2015. Cutura (2018) and Giuliana (2019) also find similar evidence, finding an average 10 basis points bail-in premium on bail-in-able bonds. Lewrick, Garralda and Turner (2019) also identify a bail-in risk premium for bail-in-able bonds issued globally.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This effect became significantly relevant after Italian authorities decided to resolve four small banks in November 2015. Cutura (2018) and Giuliana (2019) also find similar evidence, finding an average 10 basis points bail-in premium on bail-in-able bonds. Lewrick, Garralda and Turner (2019) also identify a bail-in risk premium for bail-in-able bonds issued globally.…”
Section: Introductionmentioning
confidence: 71%
“…In particular, Schafer, Schnabel, and Weder (2016) have shown that shares prices movements signal that the expectation of bail-in affects future bank returns indirectly through the effect on [increased] funding costs. Crespi, Giacomini, and Mascia (2019), Cutura (2018), Giuliana (2019), Lewrick, Garralda, and Turner (2019) document an increase in spread between bailinable and non bailinable bonds for European banks. Furthermore, the spreads appear to be sensitive to banks' riskiness, thus supporting the hypothesis that bail-in induced greater market discipline.…”
Section: Introductionmentioning
confidence: 99%
“…We document that the impact of reduced access to credit on default risk of non-financial sectors might have long-lasting effects. By studying the impact of the strengthening in the resolution framework associated with the introduction of BRRD, we complement the findings of Cutura (2021) about the perceived credibility of the newly introduced bail-in framework and provide evidence of the beneficial effects of transitioning away from a bailout regime where (expected) government recapitalizations increase banks' risk taking and default risk (Dam and Koetter (2012); Duchin and Sosyura (2014)) which can in turn increase default risk in non-financial sectors (Bersch et al (2020)). Our contribution also relates to papers analyzing the real effects of banks' bail-ins (Beck et al (2020)).…”
Section: Introductionmentioning
confidence: 91%
“…First, the event window includes the key moments of the implementation of the resolution package as, in addition to the adoption of the directive in European law, it covers both the period around January 2015 -where BRRD's provisions not related to the implementation of the bail-in tool came into force -and the period around January 2016 where the Directive became fully binding for the regulation of EU banks' bail-ins. Second, Cutura (2021) documents that the threat of an enforcement of bail-in powers by resolution authorities was perceived as credible by investors given that banks' unsecured corporate bonds maturing after January 2016, and thus subject to the bail-in tool, started trading with a positive spread over their control group, i.e., unsecured corporate bonds from the same issuers but maturing before 2016, following the introduction of the BRRD.…”
Section: Impact Of a Strengthening In The Resolution Framework For Fa...mentioning
confidence: 99%
See 1 more Smart Citation